Analisis Tingkat Kepuasan dan Pengalaman Pengguna Aplikasi Bappedasmartservice Menggunakan Metode SUS - Yahya Rizki Imansyah; Noordin Asnawi (CV. Multi Kreasi Media, 2026)
This study aims to analyze the level of satisfaction and user experience of the Bappedasmartservice application at the Madiun Regency Public Order Agency (Satpol PP) and Fire Department. The System Usability Scale (SUS) method was used, using a quantitative descriptive approach through observation and questionnaires distributed to six active users of the application. The measurement results showed an average SUS score of 73.3, which falls into the